Determination of rate of coastal erosion at Pantai Sabak, Kelantan, Malaysia using global position system - Ithnin, Hamirdin; Ahmad Baharom, Azmi (2004)
Pantai Sabak in Kelantan has been experiencing severe coastal erosion for quite some time, and quite a lot of studies had been done on the subject. The rate of erosion that is raging the coast is of prime importance due to the fact that a lot planning can be arranged before hand if the rate is known. This study measured the GPS locations of points along the selected portions of the coast. By using these GPS locations and integrating them with data from topographic maps, the distances of the advance of the coast were calculated. The rate of the erosion was then determined. The study also indulged in time sequence of the erosion rate by using data from topographic maps published as far back in time as available. Thus a more comprehensive picture of the erosion phenomenon of the State of Kelantan can be adduced from this study.